2020
DOI: 10.3390/su12219245
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Agile Project Management Practices in Non-Software SMEs: A Case Study of a Slovenian Medium-Sized Manufacturing Company

Abstract: In today’s highly dynamic and unpredictable project environment, companies need to be able to manage changes quickly and effectively, otherwise, the final product will not be current and will only go to waste. Traditional project management approaches that focus on planning are no longer efficient and companies are forced to adopt new ways of working. As a result, more flexible agile project management (APM) approaches have emerged over the last decades. Originally developed for the software industry, APM is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Indeed, the implementation of a successful cost management system depends not only on the costing method used but also on elements related to the organizational structure (e.g., the characteristics of the available information systems) and the organizational culture (e.g., engagement, management, and cost consciousness) [37,65]. For instance, the consensus among the different stakeholders is vital, since cost management influences operational, tactical, strategic, financial, and quality issues, which are linked to all levels of management and operation in the organization [70,71]. In the case study presented here, the use of the Scrum methodology promoted, since the very beginning of the process, a high involvement of all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the implementation of a successful cost management system depends not only on the costing method used but also on elements related to the organizational structure (e.g., the characteristics of the available information systems) and the organizational culture (e.g., engagement, management, and cost consciousness) [37,65]. For instance, the consensus among the different stakeholders is vital, since cost management influences operational, tactical, strategic, financial, and quality issues, which are linked to all levels of management and operation in the organization [70,71]. In the case study presented here, the use of the Scrum methodology promoted, since the very beginning of the process, a high involvement of all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…This is rather surprising, concerning SMEs account for the majority of businesses worldwide. The few existing studies indicate that the implementation of APM in SMEs is feasible but much more challenging than in larger enterprises [17,18]. Both Edwards et al [17] and Žužek et al [18] showed that ensuring fully dedicated team members, which represents an important element of APM, is almost impossible in SMEs.…”
Section: Hybrid Modelsmentioning
confidence: 99%
“…In recent years, various hybrid models combining traditional and APM approaches have been developed, and studies show that there are many benefits to such a combination [15,16]. However, most of the studies have been conducted in large companies [17], and there is a great concern that the existing hybrids are not appropriate for SMEs [18].…”
Section: Introductionmentioning
confidence: 99%
“…As Beta has not implemented an agile approach yet, this principle was assessed to be not fulfilled. (6) Corresponds with the agile manifesto's principle V. Also, because Beta has not implemented an agile approach yet, this principle was assessed to be not fulfilled. ( 7) Also corresponds best with V. The conducted interviews made it clear that the management is interested in the incorporation of agile development principles and sees advantages to powertrain development.…”
Section: Procedural Model For Assessment Of Project Development Approach Balancementioning
confidence: 99%
“…Nevertheless, Žužek et al (2020) claimed that several companies from different industries outside the software sector have already adopted agile principles for their product development approaches despite those restrictions. The authors demonstrated that only implementing separate principles at an SME allows for achieving significant benefits: improved communication, faster detection of discrepancies, more effective problem-solving, and greater flexibility [6]. Volkswagen, for example, is certainly committed to agile working methods as more people in the company are using related principles.…”
Section: Introductionmentioning
confidence: 99%